INMATES INCARCERATION AND FAMILY SUPPORT AS PRECURSORS OF PRISON RECIDIVISM IN NIGERIA - Shobola, Adeola; Ajeigbe, Taiwo .O. (European Scientific Journal, ESJ, 2015)
The study identified the common criminal offences that lead people to prison in Nigeria, it identified the people that give supports to the inmates and examined the kind of support inmates receive in prison and it also determined the extent the supporting roles received from family can prevent the inmates from returning to prison. These were with a view to assisting prisoners from returning back to prisons and thereby reducing the rate of criminal activities in the society. A counselling rehabilitation group of 13 male and 22 female inmate volunteers from one of the prisons in Nigeria were used in the study. A questionnaire was designed to elicit information on the objectives stated. The results of the study showed that stealing out of other reasons was the most common reason for being in prison (28.6%). Also, it was revealed that 80% of the inmates claimed they received supports from siblings while in prison, and 85.7% of them received sympathy support from relatives. Finally, it was revealed that 23 inmates representing 65.7% had low tendency of wanting to return to prison, as against 34.3% who displayed high tendency of wanting to return to prison as a result of the supports received from relations. It was concluded that family support if well applied with support of the government and significant others in the society will assist the prisoners to cope with life after prison and reduce the rate at which people commit crime in the society.